The Psychometric Properties of a Romanian Version of the Centrality of Religiosity Scale (CRS 15) - Huza Gheorghe (Religions, 2018)
Objective: The aim was to validate a Romanian version of the Centrality of Religiosity Scale (CRS 15) and to determine its psychometric properties in religious and highly religious people. Methods: A cross-sectional survey was conducted in different religious confessions. The sample consisted of 146 (67.9%) Orthodox, 58 (27.0%) Seventh-day Adventists, 3 (1.4%) Catholics, one (0.5%) Pentecostal, and 7 (3.4%) others. Data were collected on the Romanian version of the Centrality of Religiosity Scale (CRS 15), the Religious Belief Assessment Questionnaire (CACR), and the Moral Behavior Assessment Questionnaire (CACM). Results: The scale’s reliability analysis revealed an overall Cronbach’s alpha of 0.93. This demonstrated acceptable internal consistency. The Spearman correlation between the CRS scale’s total score and that of the Intimate and Expressive Religious Belief Assessment Questionnaire indicated positive levels of convergent validity. The Receiver Operating Characteristics (ROC) revealed good discriminative validity and the confirmatory analysis revealed a satisfactory fit. Conclusions: The validated Romanian version of the Centrality of Religiosity Scale (CRS 15) is a valid and reliable measure in detecting the centrality of religiosity.